2013
DOI: 10.1002/bio.2505
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent gelatin nanospheres by encapsulating CdSe quantum dots

Abstract: Quantum dots (QDs) have been encapsulated within gelatin nanoparticles (GNPs), which gives GNPs fluorescent properties and improves the biocompatibility of QDs. Hydrophilic CdSe QDs were produced through thermodecomposition following the ligand-exchange method, and were then encapsulated in GNPs. The results of high-resolution transmission electron microscopy and transmission electron microscopy show that CdSe QDs and QDs-encapsulated GNPs (QDs-GNPs) have average diameters of 5 ± 1 and 150 ± 10 nm, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…37 Moreover, gelatin was also used as the encapsulant of QDs to improve biocompatibility. 38,39 Recently, the fluorescent nanocompsites constructed by assembling CdSe QDs on the exterior of gelatin nanospheres were reported by Chen et al 40 In our paper, gelatin is served as the capping agent, along with TGA. The luminescent AgInS 2 core QDs were first prepared, and their PL intensity was surpassingly enhanced after ZnS coating.…”
Section: Introductionmentioning
confidence: 93%
“…37 Moreover, gelatin was also used as the encapsulant of QDs to improve biocompatibility. 38,39 Recently, the fluorescent nanocompsites constructed by assembling CdSe QDs on the exterior of gelatin nanospheres were reported by Chen et al 40 In our paper, gelatin is served as the capping agent, along with TGA. The luminescent AgInS 2 core QDs were first prepared, and their PL intensity was surpassingly enhanced after ZnS coating.…”
Section: Introductionmentioning
confidence: 93%
“…This finding suggests the QDs covalently bind into the GNs through the reaction between the amine groups of cysteamine modified on the QDs and the carboxylic groups on the exterior of the GNs. Due to the covalent bonding, the hybridization performed post nanoparticle synthesis will not affect the drug loading process nor contribute to the release of QDs as seen in the method described by Chen et al [27].…”
Section: Resultsmentioning
confidence: 99%
“…44 Our previous results indicated that no significant toxic effect is imposed on cells when the concentration of GNs is up to 5 mg/mL. 45 With further increasing the concentration of MUA-QDs up to 6.25 mg/mL, the cell viability dramatically decreases to 20%. Meanwhile, the relative cell viability (%) drops to 50% when the concentration of QDs-GNs increases up to 25 mg/mL, which might be related to the negative interference of fluorescent detection caused by the high concentration of nontransparent QDs-GNs.…”
Section: ■ Experimental Sectionmentioning
confidence: 97%